(untitled) (Swiss Medical Weekly, 2011)
Macroautophagy is a main catabolic pathway of eukaryotic cells, delivering cytoplasmic constituents for lysosomal degradation. Originally described as a starvation response, it has now been realised that macroautophagy supports many aspects of innate and adaptive immunity by facilitating innate pathogen detection and antigen presentation, as well as pathogen clearance and lymphocyte expansion. In the first half of this review, we summarise new insights into substrate selection and macroautophagic support of vesicular transport pathways, which underlie macroautophagic regulation of afferent and efferent immunity to pathogens, as outlined in the second half of the review. Applying this increased mechanistic understanding to infectious disease settings should allow us to identify further pathways for pathogen restriction, which can be explored for therapeutic manipulations of macro-autophagy.